2018
DOI: 10.3389/fnbot.2018.00040
|View full text |Cite
|
Sign up to set email alerts
|

Kick Control: Using the Attracting States Arising Within the Sensorimotor Loop of Self-Organized Robots as Motor Primitives

Abstract: Self-organized robots may develop attracting states within the sensorimotor loop, that is within the phase space of neural activity, body and environmental variables. Fixpoints, limit cycles and chaotic attractors correspond in this setting to a non-moving robot, to directed, and to irregular locomotion respectively. Short higher-order control commands may hence be used to kick the system from one self-organized attractor robustly into the basin of attraction of a different attractor, a concept termed here as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Valencia Urbina et al investigated the behavior of two-wheeled robots in a Braitenberg-style obstacle avoidance setup, but with a controller based on the connectome of C. elegans . In a general context, two-wheeled robots have been used for a wide range of purposes, such as the emergence of kick control (Sándor et al, 2018 ). Here, Valencia Urbina et al showed, that it is possible to transfer a biological network of neurons to a functioning robotic application.…”
Section: Self-organized Locomotionmentioning
confidence: 99%
“…Valencia Urbina et al investigated the behavior of two-wheeled robots in a Braitenberg-style obstacle avoidance setup, but with a controller based on the connectome of C. elegans . In a general context, two-wheeled robots have been used for a wide range of purposes, such as the emergence of kick control (Sándor et al, 2018 ). Here, Valencia Urbina et al showed, that it is possible to transfer a biological network of neurons to a functioning robotic application.…”
Section: Self-organized Locomotionmentioning
confidence: 99%
“…where k is a spring constant and x ( a ) and x ( t ) , respectively, are the actual and the target positions of the wheel in terms of a projection to the ground (Sándor, Nowak, Koglin, Martin, & Gros, 2018). Note that the angle φ , which enters the right-hand side of equations (1) and (2) as cos ( φ ) , is the measured, actual angle of the wheel.…”
Section: Locomotive Principlesmentioning
confidence: 99%
“…This is not a problem for simulated robots, for which ω is a directly accessible variable. To obtain a reliable estimate of the instantaneous angular velocity for real-world robots working with duty cycles of the order of 20 Hz would, however, be a challenge (Sándor, Nowak, Koglin, Martin, & Gros, 2018).…”
Section: Locomotive Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-organizing principles may be implemented within the sensorimotor loop [10], which is comprised of environment, body, actuator and sensory readings, with the latter being restricted in the pure case to propiosensation, viz to the internal state of the robot. The attractors self-stabilizing in the sensorimotor loop may then give rise to complex patterns of regular and of chaotic motion primitives [15], which can be selected in a second step using 'kick control' [16]. From a general perspective, kick control is an instance of a higher-level control mechanism exploiting the reduction in control complexity provided by morphologically computing robots [17,18].…”
Section: Introductionmentioning
confidence: 99%